Immunological and pathological adverse effects of avian influenza virus subtype H9N2 infection in aflatoxicated-broiler chickens - ELLAKANY, H.F.; ABD-ELHAMID, H.S.; TANTAWY, L.A.; ELSAMADONY, H.A.; ELBESTAWY, A.R.; GADO, A.R.; EL-SAYED, Y.S.; ISMAEL, H.S. (Journal of the Hellenic Veterinary Medical Society, 2020)
Aflatoxin B1 (AFB1) is a metabolic product of the Aspergillus spp. of molds, which grow on several feedstuffs stored in hot moist conditions. It is one of the immunosuppressive agents that might influence the pathogenesisof avian influenza virus (AIV) subtype H9N2 in broilers, which can exacerbate the disease outcomes. The immunological, biochemical and pathological adverse health effects of an interaction between low levels of dietary aflatoxins (AFs) and H9N2 infection in broiler chickens were investigated. One hundred and eighty of unvaccinated 1-day-old COBB chicks were, therefore, raised for 35 days in the following treatment groups: control, AFs, AFs+H9N2, and H9N2. AFs in the basal diet was added at 200 ppb starting from the first day of age, while H9N2 virus was intra-nasally installed at a dose of 100 μl of 106 EID50/bird of allantois fluid at 23rd day. Humoral and cell-mediated immune responses were evaluated. Evidence of H9N2-AIV viral shedding was also detected. It has been observed that concurrent exposure of AFs and H9N2 virus negatively affected chicken performance traits i.e. lowered feed intake and body weights with exaggerated respiratory and digestive disturbances, and 20% mortality rate. Ten days’ post H9N2 infection, significant (p≤ 0.05) increment in serum transaminases (AST and ALT) and falling in cell-mediated immunity i.e. total leukocyte count, lymphocyte transformation activity and macrophage phagocytic activity were detected. Additionally, AFs+H9N2 significantly (p≤ 0.05) lowered H9N2-HI titers (5.5 Log2) than H9N2 alone (6.3 Log2). Pathologically, aflatoxicated chickens showed hydropic degeneration, hepatocytic vacuolation and necrosis of liver tissues with nephrosis and urates deposition in ureters, as well as bursal and thymic lesions, which were potent in H9N2–inoculated chickens. AFs exposure increased the incidence and titer of H9N2 viral shedding. It could be concluded that dietary contamination with AFs even at very low levels has explanatory effect in H9N2–inoculated broilers, and vice versa.